Relationship between the use of nonpharmaceutical interventions and COVID-19 vaccination among U.S. child care providers: A prospective cohort study. Issue 31 (29th July 2022) - Patel, Kavin M.; Shafiq, Mehr; Malik, Amyn A.; Cobanoglu, Ayse; Klotz, Madeline; Eric Humphries, John; Lee, Aiden; Murray, Thomas; Wilkinson, David; Yildirim, Inci; Elharake, Jad A.; Diaz, Rachel; et al.
Abstract: Background: The relationship between the use of nonpharmaceutical interventions and COVID-19 vaccination among U.S. child care providers remains unknown. If unvaccinated child care providers are also less likely to employ nonpharmaceutical interventions, then a vaccine mandate across child care programs may have larger health and safety benefits. Methods: To assess and quantify the relationship between the use of nonpharmaceutical interventions and COVID-19 vaccination among U.S. child care providers, we conducted a prospective cohort study of child care providers ( N  = 20, 013) from all 50 states, the District of Columbia, and Puerto Rico. Child care providers were asked to complete a self-administered email survey in May-June 2020 assessing the use of nonpharmaceutical interventions (predictors) and a follow-up survey in May-June 2021 assessing COVID-19 vaccination (outcome). Nonpharmaceutical interventions were dichotomized as personal mitigation measures (e.g., masking, social distancing, handwashing) and classroom mitigation measures (e.g., temperature checks of staff/children, symptom screening for staff/children, cohorting). Results: For each unendorsed personal mitigation measure during 2020, the likelihood of vaccination in 2021 decreased by 7% (Risk Ratio = 0.93 [95% CI 0.93 – 0.95]). No significant association was found between classroom mitigation measures and child care provider vaccination (Risk Ratio = 1.01 [95% CI 1.00–1.01]). Conclusions: Child care providers who used fewer personal mitigation measures were also less likely to get vaccinated for COVID-19 as an alternative form of protection. The combined nonadherence to multiple types of preventative health behaviors, that is, both nonpharmaceutical interventions and vaccination, among some child care providers may support a role for mandatory vaccination to achieve pandemic control.